PP89 The Investigation And Development Of A National Formulary Monitoring System Across Wales. (December 2021) - Boldero, Richard; Curran, Thomas; Haines, Kath; Morton, Miranda; Routledge, Phil A.
Abstract : Introduction: The New Treatment Fund (NTF), launched in January 2017, aims to support the faster introduction of new medicines recommended by the National Institute for Health and Care Excellence (NICE) and the All Wales Medicines Strategy Group (AWMSG). The NTF requires seven health boards and one trust to make recommended medicines available within 60 days of any positive recommendation decision. The project goal was to develop a system for demonstrating how monitoring the NTF improves medicines access for the people of Wales. Methods: The process was derived via a series of task and finish group meetings with relevant stakeholders. The monitoring criteria were agreed through a collaborative expert approach using a nominal group technique. This determined a minimal dataset of formulary status, which included time to formulary addition. Pre-NTF medicines data (n = 59) were available for a six-month period. Results: By the three-year milestone of the NTF, the average time taken for newly recommended medicines (n = 219) to become available to patients across Wales had decreased by eighty-five percent from 90 to 13 days (p < 0.01). Conclusions: An innovative and robust system has been created for accurately monitoring the formulary addition of medicines within the NTF, supporting the rapid and comprehensive uptake of medicines deemed clinically and cost effective by NICE and the AWMSG.